Contradictions and emptiness all the way down? Book review: Markus Gabriel and Graham Priest,“Everything and Nothing”, Polity Press, 2022 - De Oliveira Barbalho, Pedro Augusto (Logic and Logical Philosophy, 2024)
Markus Gabriel’s pluralism and Graham Priest’s monism can be considered new forms of skepticism in contemporary philosophy. Gabriel considers ‘emptiness’ and Priest ‘nothingness’ as safe havens for logic and philosophy. In the same way, traditional skeptics also considered nothing secure. Furthermore, we observe in this book that whilst both Priest and Gabriel present rather eloquent theories, they nevertheless lack more substantial proofs, much like many important theories in philosophy, such as Leibniz’s monadology.